37. Risk Factors for Granulomatous Pneumonia Incidence in Lampung Breeding Farm - Joko Susilo; Enny Saswinyanti; Teuku Fadrial Karmil (Jurnal Medika Veterinaria, 2019)
Complex respiratory disease in the calf (enzootic calves pneumonia) is a complex respiratory disease (bovine respiratory disease complex/BRDC) caused by co-infection with viral, bacterial or fungal pathogens. Granulomatous pneumonia is one of the dominant lesions in BRDC that characterizes the infection of Mycoplasma bovis, a bacterium that is very strong against phagocytosis of immun cells. This study aims to determine the presence of risk factors associated with the incidence of granulomatous pneumonia. This study used secondary data from Laboratory of Pathology in Balai Veteriner Lampung, Sample collection in 2015-2017 period from one of the breeding farm in Lampung.  Data is processed by calculating frequency, tables and logistic regression in Epi-info tools.  The frequency of granulomatous pneumonia at the age of pre weaning and weaning was 63.06% and 36.94%, breed Wagyu and Brahman cross (76.12% and 23.88%), as well as males and females (61.01% and 38.99%). The results of measurements with Epi-info show that the age factor (Odds ratio = 2.16, 95% CI = 1.51-3.09) and breeds (Odds ratio = 1.52, 95% CI = 1.003-2.31) were associated with the incidence of granulomatous pneumonia. Based on the results of research that Wagyu calf and weaning age are more at risk of granulomatous pneumonia.